Interferons and viruses induce a novel truncated ACE2 isoform and not the full-length SARS-CoV-2 receptor - Onabajo, Olusegun O.; Banday, A. Rouf; Stanifer, Megan; Yan, Wusheng; Obajemu, Adeola; Santer, Deanna M.; Florez-Vargas, Oscar; Piontkivska, Helen; Vargas, Joselin M.; Ring, Timothy J.; Kee, Carmon; Doldan, Patricio; et al. (Nature genetics, 2020)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which causes COVID-19, utilizes angiotensin-converting enzyme 2 (ACE2) for entry into target cells. ACE2 has been proposed as an interferon-stimulated gene (ISG). Thus, interferon-induced variability in ACE2 expression levels could be important for susceptibility to COVID-19 or its outcomes. Here, we report the discovery of a novel, transcriptionally independent truncated isoform of ACE2, which we designate as deltaACE2 (dACE2). We demonstrate that dACE2, but not ACE2, is an ISG. In The Cancer Genome Atlas, the expression of dACE2 was enriched in squamous tumors of the respiratory, gastrointestinal and urogenital tracts. In vitro, dACE2, which lacks 356 amino-terminal amino acids, was non-functional in binding the SARS-CoV-2 spike protein and as a carboxypeptidase. Our results suggest that the ISG-type induction of dACE2 in IFN-high conditions created by treatments, an inflammatory tumor microenvironment or viral co-infections is unlikely to increase the cellular entry of SARS-CoV-2 and promote infection.